2019
DOI: 10.1177/1066896919830509
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathologic Subtyping of Urothelial Bladder Carcinoma in Young Patients

Abstract: Urothelial cancer is a heterogeneous disease with different molecular pathways that produce distinct molecular subtypes with specific characteristics and patient survival outcomes that require different therapeutic methods. Urothelial tumors in young patients appear to have distinct genetic features compared with their counterparts in older patients. Using a Lund subtype-specific immunohistochemistry panel, we performed molecular subtype profiling of an urothelial carcinoma case series (n = 49) in patients you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Since patients with higher stage grade have higher mortality [19], the statistically significant difference between stages and grades between the age groups may in part explain the differences in BC-specific mortality risk observed -in the current study the <50 s had more cTa and low grade tumours compared to their older counterparts, as also reported (for grade) by both de la Calle et al [5] and Telli et al [20]. These differences in stages and grades may suggest different disease biology between the age groups; hence, investigating the distribution of taxonomic subgroups is of merit for further future research, similar to that of Shelekhova et al [21]. Here the authors concluded that more aggressive molecular subtypes were more frequent in older patients.…”
Section: Discussionsupporting
confidence: 83%
“…Since patients with higher stage grade have higher mortality [19], the statistically significant difference between stages and grades between the age groups may in part explain the differences in BC-specific mortality risk observed -in the current study the <50 s had more cTa and low grade tumours compared to their older counterparts, as also reported (for grade) by both de la Calle et al [5] and Telli et al [20]. These differences in stages and grades may suggest different disease biology between the age groups; hence, investigating the distribution of taxonomic subgroups is of merit for further future research, similar to that of Shelekhova et al [21]. Here the authors concluded that more aggressive molecular subtypes were more frequent in older patients.…”
Section: Discussionsupporting
confidence: 83%
“…The last patient with pT2 underwent radical cystectomy and s-pouch diversion with the preservation of the genital organs. Urothelial tumors in young patients have distinguishable genetic characteristics compared with older patients based on a study that used a Lund subtype-specific immunohistochemistry panel to examine the molecular subtypes of a urothelial carcinoma among 49 patients aged <45 years [ 13 ] . The study revealed that 80% of patients had molecular urothelial-like A subtypes, which are characterized by improved recurrent-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancer diagnosis and treatment in young patients are challenging because obligatory close follow-up that includes regular cystoscopies, urinary cytology tests, and pyelographies is recommended to evaluate the upper urinary tracts [12]. Several published articles have discussed behavioral and clinicopathologic patterns for this condition [12][13][14][15][16]. A retrospective study involving five patients aged 24 years (±2.83 years) examined the specific characteristics of bladder cancer [12].…”
Section: Discussionmentioning
confidence: 99%
“…Shelekhova et al, performed molecular subprofiling on 49 tumours and found significantly more aggressive molecular subtypes in patients between the ages of 30 and 45 compared with patients between 20 and 29 years. 29 Owen et al, analyzed tumours in patients under the age of 19 years for alterations in DNA hypermethylation which can result in aberrant gene silencing, and compared these with matched lesions in patients aged 19 to 45 and also older patients with a median age of 78 years. They found significantly less methylation in the youngest group compared with the other groups, but no significant difference between the older two groups (34.4% vs. 60.0% vs. 52.3%).…”
Section: Discussionmentioning
confidence: 99%